2020
DOI: 10.1126/science.aay0939
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of ribosomal protein expression and translation promotes breast cancer metastasis

Abstract: Circulating tumor cells (CTCs) are shed into the bloodstream from primary tumors, but only a small subset of these cells generates metastases. We conducted an in vivo genome-wide CRISPR activation screen in CTCs from breast cancer patients to identify genes that promote distant metastasis in mice. Genes coding for ribosomal proteins and regulators of translation were enriched in this screen. Overexpression of RPL15, which encodes a component of the large ribosomal subunit, increased metastatic growth in multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
237
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(246 citation statements)
references
References 62 publications
9
237
0
Order By: Relevance
“…They induce EMT through the transcriptional downregulation of E-cadherin (CDH1) while upregulation of mesenchymal-specific genes of Snail Family Transcriptional Repressor 1/2 (SNAI1/ SNA2), Zinc Finger E-Box Binding Homeobox 1/2 (ZEB1/2), Twist basic helix-loop-helix transcription factor 1/2 (TWIST1/2), Forkhead Box C1/2 (FOXC1/2), Transcription factor 3 (TCF3), Goosecoid Homeobox (GSC) [11]. Additional to these transcription factors, a substantial number of recent studies provided evidence in the involvement of other types of proteins including proto-oncogene Cellular Oncogene Fos (c-FOS), Zinc finger protein 367 (ZNF367), ribosomal protein RPL15, RNA-binding protein A-Kinase Anchor Protein (AKAP8) in regulation of breast cancer metastasis [12][13][14][15][16]. However, for understanding the cellular transition mechanisms lying in the heart of breast cancer metastasis, it is very important to shed light over the epigenetic mechanisms besides these regulations.…”
Section: Introductionmentioning
confidence: 99%
“…They induce EMT through the transcriptional downregulation of E-cadherin (CDH1) while upregulation of mesenchymal-specific genes of Snail Family Transcriptional Repressor 1/2 (SNAI1/ SNA2), Zinc Finger E-Box Binding Homeobox 1/2 (ZEB1/2), Twist basic helix-loop-helix transcription factor 1/2 (TWIST1/2), Forkhead Box C1/2 (FOXC1/2), Transcription factor 3 (TCF3), Goosecoid Homeobox (GSC) [11]. Additional to these transcription factors, a substantial number of recent studies provided evidence in the involvement of other types of proteins including proto-oncogene Cellular Oncogene Fos (c-FOS), Zinc finger protein 367 (ZNF367), ribosomal protein RPL15, RNA-binding protein A-Kinase Anchor Protein (AKAP8) in regulation of breast cancer metastasis [12][13][14][15][16]. However, for understanding the cellular transition mechanisms lying in the heart of breast cancer metastasis, it is very important to shed light over the epigenetic mechanisms besides these regulations.…”
Section: Introductionmentioning
confidence: 99%
“…S8). Overexpression of genes encoding ribosome protein components in CTCs has recently been shown to contribute to tumor metastasis (30).…”
Section: Reduced Ck Expression In Cancer Cells Is Often Associated Wimentioning
confidence: 99%
“…Ribosome biogenesis can increase the size of nucleolar organizing regions (NORs) which have long been used as a marker of tumor cell proliferation that negatively correlates with patient survival 39 . Richard Y. et al indicated that the increasing of ribosomal content in epithelial cell fates may enhance their metastatic potential in breast cancer 40 . Studies also demonstrated that drugs inhibiting ribosome biogenesis might provide a feasible therapeutic method for cancer treatment 41 .…”
Section: Dicussionmentioning
confidence: 99%